ANALISA DAN DESAIN KONTEN INSTAGRAM YANG MENARIK DAN BERDAMPAK POSITIF PADA INTERAKSI PENGGUNA: ANALYZE AND DESIGN INTERESTING INSTAGRAM CONTENT AND HAVE A POSITIVE IMPACT ON USER INTERACTION - Sri Mulyani; Purwatiningtyas Purwatiningtyas; Yunus Anis (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2024)
As one of the most popular social media platforms today, Instagram has more than one billion monthly active users. This is a great opportunity for users to interact with each other, share content, and build rapport. However, to achieve this, the right strategy is needed to create interesting content according to user interests. In line with the aim of this research, to obtain interesting content that has a positive impact on user interaction, researchers use the Design Thinking method which involves users and stakeholders in Instagram accounts. This research was conducted by including three content designs that provide the best insight from more than sixty Instagram content designs posted on accounts in the period 5 June to 6 September 2023 on the Graphic Multimedia Engineering Technology (TRMG) study account @trmg_unisbank which was used as an object. From the analysis and design of Instagram content, it managed to reach 20,275 followers with 80 accounts and 20,195 non-follower accounts. This means that attractive content design can have a positive impact on user engagement. This content is built by exploring the target audience, understanding user interests, using images and design, including interesting captions and relevant hashtags, and conveying useful information (education).